STUDY OF PHRASEOLOGY ISSUES IN WORLD LINGUISTICS AND TRANSLATION STUDIES (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
The word "phraseology" is derived from the Greek word "phrasis," which means a device of speech. The word has two meanings. The first is a term used to describe a fixed layer of linguistics, that is, a particular layer that studies phraseological units, and the second is a term that serves to describe a set of phraseological units. The term phraseological unit was first introduced into linguistics by V.V.Vinogradov. Along with the terms phraseological unit and phraseology, the terms idiom and idiomatics are also used.